Traditional gold mining in the highlands of Ethiopia: Its effect on soil loss and possible reclamation measures - Zenebe, Meaza; Birhane, Emiru; Teka, Kassa; Haile, Mitiku; Tadesse, Tewodros; Taye, Gebeyehu (Journal of Degraded and Mining Lands Management, 2024)
Traditional gold mining (TGM) is among the off-farm income sources of smallholder communities in the highlands of Ethiopia. However, information on their impact on land degradation, taking soil loss as a key indicator, was scant. Hence, this study aimed at i) analyzing local communities’ attitudes toward TGM practice, ii) TGM impact on soil loss, and iii) possible restoration measures for the degraded gold-mined landscapes. For the evaluation of community perceptions, 96 beneficiaries were selected from three gold mining sites following stratified random sampling techniques. Soil loss measurement was done through measurement of i) the mass of soil excavated and transported to the river (TR) from 96 individuals and ii) soil volume excavated in 45 excavated soil pits (EP). Descriptive statistics and one-way ANOVA were used to analyze soil loss data, while community perception was analyzed qualitatively. The survey results indicated that the average soil loss from TR and EP were 6,075.97±8.9 t ha-1 yr-1 and 32,549.99±753.68 t ha-1, respectively. The magnitude of soil loss also showed a significant (p<0.001) difference among the three sites. Due to a lack of awareness and hiding the reality, most of the gold miners believe that TGM practice has no negative impact on the soil resource, and no post-mined reclamation strategy is implemented. It can be concluded that the existing TGM practices are not done in an environmentally friendly approach and result in adverse soil loss. Hence, stabilizing the topography of the mined sites via backfilling of mined pits and topsoil conservation and amendment measures can be suggested.